A Technique to Estimate the Mobile Position and Rotation - Anh, Trinh Hien; Hung, Trinh Xuan; Toan , Ha Manh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2022)
Nowadays, almost all applications, especially augmented reality (AR) applications, run on the web. In these applications, determining the position and rotation of the mobile device is an indispensable basic step. The speed and accuracy of this work greatly affect the quality of the user experience. Therefore, estimating the rotational position of mobile devices on the Web is necessary and meaningful in practice. In this paper, we propose a way to estimate the position and rotation of the mobile device using the image of the marker obtained from the camera combined with the data from the device’s tilt angle sensor. The proposal has been experimentally installed and evaluated for performance on Web Assembly, Java Script, and C++ platforms. Along with that, to ensure objectivity, we compared the speed and calculation error of the proposed technique with the P3P and PnP techniques installed in the OpenCV open-source library. We also use the proposal method to develop the Virtual Museum application for the Vietnam National Museum of Nature